2023
DOI: 10.1001/jamaophthalmol.2023.2415
|View full text |Cite
|
Sign up to set email alerts
|

Social Risk Factor Associations With Presenting Visual Acuity in Patients With Microbial Keratitis

Abstract: ImportanceNeighborhood-level social risk factors may contribute to health disparities in microbial keratitis (MK) disease presentation. Understanding neighborhood-level factors may identify areas for revised health policies to address inequities that impact eye health.ObjectiveTo investigate if social risk factors were associated with presenting best-corrected visual acuity (BCVA) for patients with MK.Design, Setting, and ParticipantsThis was a cross-sectional study of patients with a diagnosis of MK. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(95 reference statements)
0
13
0
Order By: Relevance
“… 8 Social risk groups were associated with vision of <20/40, again consistent with prior studies showing health disparities in the risk of vision impairment. 21 Although we chose to use the average visual acuity when bilateral measurements were available, sensitivity analyses (data not shown) suggested similar results when we chose the better visual acuity, a randomly selected eye, as well as only right eyes. Last, we did not find an association between social risk group and the most severe form of diabetic retinopathy, proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 96%
“… 8 Social risk groups were associated with vision of <20/40, again consistent with prior studies showing health disparities in the risk of vision impairment. 21 Although we chose to use the average visual acuity when bilateral measurements were available, sensitivity analyses (data not shown) suggested similar results when we chose the better visual acuity, a randomly selected eye, as well as only right eyes. Last, we did not find an association between social risk group and the most severe form of diabetic retinopathy, proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 96%
“…Our group has reported on the association between ADI and presenting visual acuity in patients with corneal ulcers. 16 Among 2990 patients with corneal ulcers, for every 10-unit worse ADI score (measured on a 100-unit scale) there were 30% increased odds of presenting with best corrected visual acuity of less than 20/40 (OR, 1.30; 95% CI, 1.25–1.35; P < 0.001), after controlling for age, self-reported sex, self-reported race, and self-reported ethnicity. 16 Yusuf and colleagues 47 reported that patients who lived in the 30% most disadvantaged neighborhoods had 44% increased odds of non-adherence to initial diabetic retinopathy screening compared to patients living in more advantaged neighborhoods (OR = 0.65; 95% CI, 0.44–0.97; P = 0.035) after adjusting for age, race, and insurance status.…”
Section: Methodsmentioning
confidence: 99%
“…Our group evaluated the association between neighborhood-level transportation access and presenting visual acuity among patients presenting to eye clinics for microbial keratitis. 16 There were increased odds of presenting with visual acuity less than 20/40 in patients with microbial keratitis when a patient's neighborhood had a higher percentage of households with no car (OR = 1.25 per 1 percentage point increase; 95% CI, 1.12–1.40; P = 0.001) and a lower average number of cars per household (OR = 1.56 per one less car; 95% CI, 1.21–2.02; P = 0.003) after adjusting for age, self-reported sex, and self-reported race and ethnicity. 16 Kim et al, 17 utilizing the nationally representative National Health Interview Survey, found that transportation barriers were associated with delayed medical care in patients with glaucoma.…”
Section: Neighborhood and Built Environment Srfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to literature on systemic health, the link between vision and the neighborhood and built environment warrants further investigation . There is early literature suggesting an association between neighborhood deprivation and vision health . Individuals from neighborhoods with high deprivation scores may be at increased risk of screening positive for glaucoma and present with worse best-corrected visual acuity when experiencing microbial keratitis .…”
Section: Introductionmentioning
confidence: 94%